Word processing abilities in subjects after stroke or traumatic brain injury - Lice, Karolina (Acta clinica Croatica (Tisak), 2024)
Acquired language disorder is a common consequence of stroke and traumatic brain injury (TBI). Following the logogen model, this study investigated word processing abilities of post-stroke and post-TBI patients. Within- and between-group differences in word comprehension, naming, and reading were observed, as well as predominant errors in performance. Twenty-two post-stroke and 22 post-TBI patients were tested using tasks from the Comprehensive Aphasia Test-HR (CAT-HR). Post-TBI patients outperformed post-stroke patients in naming and reading. Both groups exhibited neologisms, phonological, semantic and unrelated errors, although in different proportions. In word comprehension and naming, post-TBI patients primarily exhibited semantic errors, whereas post-stroke patients had equally distributed phonological and semantic errors. In reading, both groups predominantly produced phonological errors. Error distribution differed only in naming, with post-TBI patients exhibiting more semantic errors than post-stroke patients. Therefore, performance in naming differentiated these groups most. Although error analysis is rather insightful, one cannot expect a particular profile of language disturbances in post-stroke and post-TBI patients. The findings obtained bear concrete clinical implications, especially those related to the role and meaning of the errors produced by the patient to determine the exact location of the processing deficits.